The curcumin analog CH-5 exerts anticancer effects in human osteosarcoma cells via modulation of transcription factors p53/Sp1 - Lima, Felipe Teixeira; Seba, Viviane; Silva, Gabriel; Torrezan, Guilherme Silva [UNESP]; Polaquini, Carlos Roberto [UNESP]; Pinhanelli, Vitor Caressato; Baek, Seung J.; Fachin, Ana Lúcia; Regasini, Luis Octavio [UNESP]; Marins, Mozart (MDPI, 2018)
Curcumin is a potential anticancer drug with poor bioavailability, which limits its clinical use as a therapeutic agent. The aim of this study was a preliminary evaluation of the curcumin analogue CH-5 as a cytotoxic agent in human osteosarcoma cell lines U2OS, MG-63, and Saos-2. CH-5 inhibited cell viability at lower concentrations than curcumin, leading to the induction of apoptosis. The cellular levels of the transcription factors p53 and Sp1 affect the expression of cellular pathways that lead to apoptosis. CH-5 increased p53 protein levels in U2OS cells and reduced Sp1 levels, with a consequent effect on the expression of their target genes DNA methyltransferase 1 (DNMT1) and growth arrest and DNA damage-inducible 45 alpha gene (Gadd45a). CH-5 repressed DNMT1 and increased Gadd45a mRNA expression, which was dependent on p53, as this effect was only observed in the colorectal cancer cell line HCT116 with active p53, but not in the isogenic p53-deficient HCT116 cells. CH-5 also reduced the protein levels of DNMT1, which led to the upregulation of Gadd45a. These results suggest that CH-5 has potentially higher anticancer activity than curcumin, which is associated with the expression of apoptosis-associated genes regulated by the transcription factors Sp1 and p53. Future work on CH-5 will define the therapeutic potential of this compound in vivo.
Keywords: Apoptosis; Curcumin; Invasion; Migration; Osteosarcoma